2011
DOI: 10.1089/nat.2011.0304
|View full text |Cite
|
Sign up to set email alerts
|

Selection of RNA Oligonucleotides That Can Modulate Human Dicer ActivityIn Vitro

Abstract: Human ribonuclease Dicer is an enzyme that excises small regulatory RNAs from perfectly or partially double-stranded RNA precursors. Although Dicer substrates and products have already been quite well characterized, our knowledge about cellular factors regulating the activity of this enzyme is still limited. To learn more about this problem, we attempted to determine whether RNA could function not only as a Dicer substrate but also as its regulator. To this end, we applied an in vitro selection method. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…2) selectively and permanently repressed the excision of miR-210 from its precursor. Our preliminary observations suggested that ATD_13.6 should be classified as allosteric inhibitor and that ATD_15.52 should be considered a competitive inhibitor [32]. Unfortunately, our earlier experiments did not reveal any molecular determinants of inhibitor specificity.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…2) selectively and permanently repressed the excision of miR-210 from its precursor. Our preliminary observations suggested that ATD_13.6 should be classified as allosteric inhibitor and that ATD_15.52 should be considered a competitive inhibitor [32]. Unfortunately, our earlier experiments did not reveal any molecular determinants of inhibitor specificity.…”
Section: Resultsmentioning
confidence: 69%
“…In a pool of hDicer-binding RNA oligomers identified by SELEX (using approximately 56-nt long oligoribonucleotides), we found molecules that inhibited pre-miRNA processing by acting as: (i) competitive inhibitors – these oligomers were cut by hDicer; and (ii) allosteric inhibitors – these molecules were not digested by hDicer [32]. Interestingly, among the selected oligomers, ATD_13.6 (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We used an oligomer RNA [26] (Supplementary Table S1) which had a great affinity for Dicer (but not cleaved by Dicer) and added it to an antisense RNA targeting MALAT-1 RNA to form an artificial small RNA (asRNA) (Supplementary Table S2) (Figure 1). The plasmid pGPU6-GFP-NEO was used to express the asRNA after the cDNA sequence of asRNA was inserted into it.…”
Section: Resultsmentioning
confidence: 99%